Health promotion in the workplace - O'Donnell, Michael Patterson, 1952- (Troy, MI : Art & Science of Health Promotion Institute, 2017)
This 5th edition, is a valuable reference for anyone who designs, manages, evaluates or studies workplace health promotion programs. Authored by a team of program managers and scholars who have designed and managed programs in several thousand settings, conducted hundreds of program evaluations, and published thousands of scientific studies on the most effective approaches, this 689 page book provides the rare combination of practical perspective combined with conservative scientific rigor.
Section I The Health Promotion Concept -- Chapter 1 Health Impact of Lifestyle and Health Promotion -- Chapter 2 The Employer's Business Case for Workplace Health Promotion -- Chapter 3 The Face of Wellness -- Section II Management Issues -- Chapter 4 How to Design and Finance Workplace Health Promotion Programs -- Chapter 5 Management Processes -- Chapter 6 Health Promotion in the Workplace Program Evaluation -- Chapter 7 Marketing and Communication Strategies -- Section III Core Theories Of Behavior Change For Motivation And Skill Building -- Chapter 8 Pursuing Health Related Goals -- Chapter 9 Transtheoretical Model -- Chapter 10 Intrinsic and Extrinsic Incentives in Workplace Health Promotion -- Chapter 11 Self-efficacy: Broad Implications for Research and Practice -- Chapter 12 Tailoring and Health Promotion in the Workplace -- Section IV Core Program FOCI: Building Skills And Creating Opportunities -- Chapter 13 Health Assessment -- Chapter 14 Enhancing Fitness and Physical Activity -- Chapter 15 Worksite Nutrition Programs -- Chapter 16 Stress Management in the Workplace -- Chapter 17 Addressing Obesity at the Workplace -- Chapter 18 Tobacco Prevention and Control in the Workplace -- Chapter 19 Health Decision Support: Health and Medical Decision Support and Chronic Condition Self-Management -- Chapter 20 Employee Assistance Programs: Serving at the Nexus of Employers and Employee Well-being -- Section V Enhancing Opportunities -- Chapter 21 Social Relationships: Harnessing their Potential to Promote Health -- Chapter 22 Transforming Organizational Cultures to Support Good Health -- Section VI Central And Emerging Trends -- Chapter 23 Special Challenges and Opportunities for Small Business.
Includes bibliographical references and index.
Keywords: Occupational health services; Health promotion